High-efficiency perovskite solar cells employing a conjugated donor–acceptor co-polymer as a hole-transporting material. Issue 44 (22nd May 2017) - Yu, Ze; Zhang, Yuchen; Jiang, Xiaoqing; Li, Xiaoxin; Lai, Jianbo; Hu, Maowei; Elawad, Mohammed; Gurzadyan, Gagik G.; Yang, Xichuan; Sun, Licheng
Abstract : In this work, we have successfully demonstrated that molecularly p-doping of donor–acceptor co-polymer PCPDTBT as an efficient hole-transporting material in perovskite solar cells with a decent power conversion efficiency of 15.1%. Abstract : In this work, we have successfully introduced 2, 3, 5, 6-tetrafluoro-7, 7, 8, 8-tetracyanoquinodimethane (F4TCNQ) as an efficient p-type dopant for donor–acceptor (D–A) co-polymer poly[2, 6-(4, 4-bis-(2-ethylhexyl)-4 H -cyclopenta[2, 1- b ;3, 4- b ′]dithiophene)- alt -4, 7(2, 1, 3-benzothiadiazole)] (PCPDTBT) as an HTM in mesoscopic perovskite solar cells (PSCs). The bulk conductivity is significantly enhanced by 4 orders of magnitude when PCPDTBT is doped with F4TCNQ (6%, w/w). UV-vis and Fourier transform infrared spectroscopy (FTIR) results indicate the occurrence of p-doping, which results in higher bulk conductivity. The high conductivity leads to an impressive overall efficiency of 15.1%, which is considerably higher than the pristine PCPDTBT based devices (9.2%). The superior performance obtained should be largely attributed to the significant enhancement of the photocurrent density strongly correlated with a more efficient charge collection. This is the highest efficiency reported so far for PCPDTBT-based PSCs. Thus, molecularly p-doping has been demonstrated to be an effective strategy for further improving the performance of a wide range of D–A and other types of polymeric HTMs in PSCs.